2015
DOI: 10.1097/prs.0000000000001449
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Skin Grafts

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 1 publication
0
17
1
Order By: Relevance
“…Our average mobility restriction time and overall keystone complication rate (19%: 3/16) is in line with other truncal and extremity keystone series. 4,14,20 Our lower extremity complication rate (43%: 3/7) was higher than the overall reported average of 9.6%. 21 However, we believe this increased rate reflects the conservative inclusion of all complications, including presumed infections treated without culture confirmation and any small, self-resolving dehiscence.…”
Section: Discussioncontrasting
confidence: 61%
“…Our average mobility restriction time and overall keystone complication rate (19%: 3/16) is in line with other truncal and extremity keystone series. 4,14,20 Our lower extremity complication rate (43%: 3/7) was higher than the overall reported average of 9.6%. 21 However, we believe this increased rate reflects the conservative inclusion of all complications, including presumed infections treated without culture confirmation and any small, self-resolving dehiscence.…”
Section: Discussioncontrasting
confidence: 61%
“…There were 2 articles reporting more than 1 keystone flap on the same patient. [ 10 , 13 ] Multiple keystone flaps on the same patient or on the same leg might affect the complication rate. Stone et al [ 10 ] reported 32 keystone flaps in 30 patients, with 2 patients having bilateral lower leg flaps.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 13 ] Multiple keystone flaps on the same patient or on the same leg might affect the complication rate. Stone et al [ 10 ] reported 32 keystone flaps in 30 patients, with 2 patients having bilateral lower leg flaps. However, there was no information on the complication about these 2 patients with bilateral lower leg flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, there is a sparsity of literature that concerns itself with the most appropriate means of periarticular wound closure. Although keystone flaps have been used previously for generic lower limb reconstruction ( 6 , 25 ) they have not been used widely in the popliteal fossa or periarticular areas to our knowledge. Alternatives to fasciocutaneous flaps such as the keystone include reconstruction with skin grafts, though these do not parallel the robust tissue coverage of local flaps and may exhibit high failure rates ( 16 ), particularly in mobile areas where graft adherence may be compromised.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that keystone flaps around the elbow, knee, and ankle joints should be used cautiously due to reduced skin laxity and a risk of dehiscence ( 30 ), and previous studies have reported wound dehiscence following full flexion at the lumbosacral area ( 25 ). In our series, we did not immobilize the joints in plaster casts, but advise bulky dressings and enforced rest until wound checks were performed 2 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%